Stability of the wall jet formed by the impingement of a single-phase jet - Özdemir, İ.B. (Archives of Mechanics, 1996)
This paper describes a theoretical investigation of the possibility that the large structures of the wall jet flow formed after oblique impingement of an axisymmetric jet were generated by the flow instabilities, so that the experimentally reported discrete frequencies were synonymous with instability modes. The wall jet flow was triple-decomposed into a time-independent, pseudolaminar motion defined by the time-averaged velocity field, upon which incoherent and coherent turbulent fluctuations were superimposed. Solution of the inviscid, one-dimensional flow equations with large coherent structures, which were modelled by spatially evolving waves, was given in detail and revealed that the distribution of the radial fluctuation intensity and the frequency of large structures compare well with the experiments justifying the deterministic nature of the coherent motion.